2010
DOI: 10.1016/j.canlet.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine interacts with copper to generate hydrogen peroxide and selectively induce cancer cell death

Abstract: A variety of metal-binding compounds have been found to exert anti-cancer activity. We postulated that N-acetylcysteine (NAC), which is a membrane-permeable metal-binding compound, might have anti-cancer activity in the presence of metals. We found that NAC/Cu(II) significantly alters growth and induces apoptosis in human cancer lines, yet NAC/Zn(II) and NAC/Fe(III) do not. We further confirmed that this cytotoxicity of NAC/Cu(II) is attributed to reactive oxygen species (ROS). These findings indicate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…In contrast, the cytotoxicity induced by 1 mM NAC plus 10 µM Cu (II) was enhanced by exogenous SOD1, and attenuated by exogenous catalase, which is consistent with toxicity due to extracellular ROS generation (data not shown, [23]). …”
Section: Fig 5 Nac Attenuates Curcumin (Cc) Plus Trolox's Cytotoxicsupporting
confidence: 58%
See 1 more Smart Citation
“…In contrast, the cytotoxicity induced by 1 mM NAC plus 10 µM Cu (II) was enhanced by exogenous SOD1, and attenuated by exogenous catalase, which is consistent with toxicity due to extracellular ROS generation (data not shown, [23]). …”
Section: Fig 5 Nac Attenuates Curcumin (Cc) Plus Trolox's Cytotoxicsupporting
confidence: 58%
“…We recently reported that NAC plus copper generates extracellular ROS, which is cytotoxic to cancer cells [23] in a manner similar to that reported for vitamin C [24]. The concept of extracellular and intracellular ROS generation and its influence on cell function has been recognized [25].…”
Section: Exogenous Sod1 and Catalase Have No Effect On Cytotoxicity Imentioning
confidence: 93%
“…We, for the first time using real-time flow cytometry, measured mitochondrial redox state by monitoring H 2 DCFDA oxidation to DCF [35] and its attenuation by known anti-oxidants, NAC and vitamin E. Unexpectedly, we found that low doses of both NAC and vitamin E had pro-oxidant activity. While pro-oxidant effects of NAC [36,37] and vitamin E [38] have previously been reported, our study conclusively linked these effects with the mitochondria. In general, antioxidants may act as pro-oxidants when reducing equivalents are depleted [39] or by interacting with redox active transition metals, e.g., Cu and Fe (both occur in substantial amounts in the mitochondria), yielding the superoxide anion and H 2 O 2 [37,40].…”
Section: Figure 10supporting
confidence: 59%
“…While pro-oxidant effects of NAC [36,37] and vitamin E [38] have previously been reported, our study conclusively linked these effects with the mitochondria. In general, antioxidants may act as pro-oxidants when reducing equivalents are depleted [39] or by interacting with redox active transition metals, e.g., Cu and Fe (both occur in substantial amounts in the mitochondria), yielding the superoxide anion and H 2 O 2 [37,40]. Moreover, the oxidation of thiol groups present in NAC by ROS can result in the formation of thiyl radicals due to insufficient regenerative reduction [36].…”
Section: Figure 10supporting
confidence: 59%
“…The cytotoxicity of clioquinol and its six analogues were examined using the MTS reagent as previously described [13]. Briefly, Raji, DHL-4 and HL-60 cells were plated in 96-well plates at 10,000 cells/well, and A2780 and Panc-1 cells at 5,000/well.…”
Section: Methodsmentioning
confidence: 99%